Creativity Alone Does Not Make a Star – Social Attributes of the Nomination of Creative Icons: Results of a Trend Study in Germany - Tang, Min; Werner, Christian H.; Hofreiter, Sebastian (Frontiers in Psychology, 2018)
Recent years have witnessed a series of studies of the nomination of the most creative persons using a cross-sectional design. Such studies only provide a “snapshot” of the creativity nomination phenomenon without being able to detect the temporal pattern of the nomination over time. The current study is among the first of such studies that use a time series design. Data were collected from German young adults in 2013 (n = 460, Mage = 28.3, SD = 9.9) and in 2017 (n = 617, Mage = 31.4, SD = 10.6). Consistent patterns emerge from the nomination of the top 10 most creative Germans: (1) Artists are predominantly represented; (2) Male creators are predominantly nominated; (3) Einstein ranks the first in both lists followed by Goethe; (4) Merkel is the only female nominee in both lists. Analysis of all nomination in both years reconfirmed the aesthetic salience and male-dominance and these patterns were more likely to occur in earlier than later nominations. Regression analysis revealed that social contribution (SC) and social acceptance (SA) each mediated the positive relation between creativity and creative fame. Further, the three-path mediation model of creativity on creative fame through SC and SA was also significant for both nomination conditions, with stronger mediating effect on the nomination from the meritorious than the aesthetic areas. Domain-specificity theories and social psychological theories were used to interpret the results.